Studi Islam Di Barat; Antara Kolonialisasi Ilmu Pengetahuan Dan Academic Oriented - Moh. Mundzir; Muhammad Aziz (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract, the golden ink incision of Islamic civilization which has long dominated theworld certainly makes Islam a phenomenon that deserves to be studied throughout theages, especially by people outside of Islam. Westerners in particular. Theyresearched, conducted studies, and made Islam as an object of study in their world ofeducation. Moreover, supported by the methodological advantages they have. As aresult, up to now, hundreds or even thousands of Islamic Studies experts have beenborn from several universities both in America and in Europe. With this background,the author wants to examine in depth related to Islamic studies in the Western world,especially in the academic world. Hopefully it can provide overall benefits. From thebackground mentioned, several problems can be formulated to be examined in thispaper, including: What is the nature of Islamic studies? What is the history of Islamicstudies in the Western world? What is the current condition of Islamic studies in theWestern academic world? From the presentation of Islamic studies in the Westernacademic world mentioned in the previous chapter, it can be concluded that: (1)Islamic Studies is an attempt to know and understand and discuss in depth about theins and outs of things related to Islam from various aspects. With the holding ofIslamic studies, it is expected to be able to improve the understanding andappreciation of the Islamic community wherever they are; (2) Islamic studies whenviewed from the perspective of the study, can be grouped into two, insider andoutsider. The study of Islam by Muslims themselves in classical times tended to usesustainable patterns from generation to generation. The pattern is experiencing a shiftin the present, which tends to be a critical pattern. While the outsider's perspective,Islamic studies are critical in various aspects because they are based on the attitude ofdefending themselves against the beliefs they have believed so far; (3) The history ofIslamic studies in the Western academic world has been around for a long time. Thelong history is decoded into three according to the purpose and content of Islamicstudies. The three stages include: theological stage, political stage and scientificstage; (4) The condition of Islamic studies in the Western academic world can be seenfrom the rise of centers of Islamic studies in various countries both in America andEurope. Many centers of Islamic studies have sprung up in the United States, Chicago,the Netherlands, Germany, London and so on. Keywords, Islamic, Western, Eastern, and Orientalist Studies